Peran Pemasaran Digital dalam Memperluas Jangkauan Pasar UMKM Lesehan Angel di Era Society 5.0 - Santi Rimadias; Bani Saad; Bintang Amanda; Liviana Putri Widianto; Gabriella Septalia Konda; Muhammad Iqbal Jehansyah; Muhammad Bagas Ardhianto (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The fluctuating shifts in consumer behavior in the Society 5.0 era are forcing the Micro, Small, and Medium Enterprises (MSMEs) sector to adopt digital tools. Based on this situation, the STIE Indonesia Banking School's community service program team implemented digital marketing tactics. This community service program aimed to expand the market share of the "Lesehan Angel" culinary stall in South Jakarta through digital marketing. Three work phases served as the mainstay of the community service program. Furthermore, the digital marketing strategy also encouraged responsive service, the delivery of engaging product information, and facilitated easy communication between businesses and customers. The use of digital marketing has been proven to expand market reach, increase customer numbers, and strengthen relationships between MSMEs and consumers. Therefore, digital marketing has become a crucial strategy for MSMEs in facing increasingly modern and technology-driven business competition. To accelerate technology adoption, the team utilized social media and culinary applications to increase brand awareness for the food stall. Through this well-structured approach, the community service team focused not only on promotional visuals but also on improving online customer service.